SME Policy Index: Western Balkans and Turkey 2016 Assessing the Implementation of the Small Business Act for Europe - OECD eBooks; Organisation for Economic Co-operation and Development; ETF.; EU.; EBRD.; SEECEL (Paris : OECD Publishing, 2016)
The SME Policy Index is a benchmarking tool designed for emerging economies to assess SME policy frameworks and monitor progress in policy implementation over time. The Index has been developed by the OECD in partnership with the European Commission (EC), the European Bank for Reconstruction and Development (EBRD), and the European Training Foundation (ETF) in 2006 for the Western Balkans. The South East European Centre for Entrepreneurial Learning (SEECEL) joined as an additional partner in 2014. The SME Policy Index has since 2006 been applied in four regions and nine assessment rounds overall. The SME Policy Index: Western Balkans and Turkey 2016 presents the results of the fourth assessment of the Small Business Act for Europe in the Western Balkans and, since 2012, Turkey. The assessment framework is structured around the ten principles of the Small Business Act for Europe (SBA). It provides a wide-range of pro-enterprise measures to guide the design and implementation of SME policies based on good practices promoted by the EU and the OECD. The Index identifies strengths and weaknesses in policy design, implementation and monitoring. It allows for comparison across countries and measures convergence towards good practices and relevant policy standards. It aims to support governments in setting targets for SME policy development and to identify strategic priorities to further improve the business environment. It also helps to engage governments in policy dialogue and exchange good practices within the region and with OECD and EU members.
Foreword and Acknowledgements -- Abbreviations and acronyms -- Executive summary -- Overview -- 2016 SME Policy Index scores for the Western Balkans and Turkey -- Policy framework and assessment process -- Economic context and the role of SMEs in the Western Balkans and Turkey -- Entrepreneurial learning and women's entrepreneurship (Dimension 1) in the Western Balkans and Turkey -- Bankruptcy and second chance for SMEs (Dimension 2) in the Western Balkans and Turkey -- Institutional and regulatory framework for SME policy making (Dimension 3) in the Western Balkans and Turkey -- Operational environment for SMEs (Dimension 4) in the Western Balkans and Turkey -- Support services for SMEs and start-ups, and public procurement (Dimensions 5a and 5b) in the Western Balkans and Turkey -- Access to finance for SMEs (Dimension 6) in the Western Balkans and Turkey -- Standards and technical regulations (Dimension 7) in the Western Balkans and Turkey -- Enterprise skills and innovation (Dimensions 8a and 8b) in the Western Balkans and Turkey -- SMEs in a green economy (Dimension 9) in the Western Balkans and Turkey -- Internationalisation of SMEs (Dimension 10) in the Western Balkans and Turkey -- Albania -- Bosnia and Herzegovina -- Kosovo -- Former Yugoslav Republic of Macedonia -- Montenegro -- Serbia -- Turkey -- Methodology for the Small Business Act assessment -- The Small Business Act assessment's scoring model for Bosnia and Herzegovina -- Organisation profiles.
Keywords: Development; Albania; Bosnia and Herzegovina; Former Yugoslav Republic of Macedonia (FYROM); Montenegro; Serbia; Turkey; Electronic books